A Regulation-Based Readiness Assessment Model for Smart City Development in Indonesia - Widyantari Febiyanti; Rizkillah Ridha (Asosiasi Doktor Sistem Informasi Indonesia, 2026)
This study addresses the lack of a smart city readiness assessment instrument that is explicitly aligned with Indonesia’s urban governance framework, particularly Government Regulation No. 59 of 2022. Existing readiness models often provide generic or technology-centred measures and do not sufficiently operationalise national regulatory requirements, limiting their utility for Indonesian local governments. To fill this gap, the study develops a regulation-based smart city readiness model comprising measurable, context-specific indicators that support readiness evaluation prior to implementation. The research adopts a Design Science Research (DSR) methodology, supported by a PRISMA-guided Systematic Literature Review to identify and synthesise candidate indicators, followed by iterative refinement. Instrument validation was conducted through expert judgement, face validity, and inter-rater reliability testing using Cohen’s Kappa. The final output is a validated readiness assessment instrument consisting of 70 indicators organised into five regulation-derived dimensions: infrastructure, facilities, public utilities, human resources, and suprastructure. Reliability results show strong inter-rater agreement (κ = 0.895), indicating robust and consistent indicator classification. The study contributes a policy-aligned readiness instrument grounded in Indonesia’s regulatory context and provides local governments with a standardised tool to assess readiness, identify development gaps, and support evidence-based planning for sustainable smart city implementation.